Sara Douda's Essence of Symbols: Expressions of Art, Culture and Faith of the Loli Community West Sumba - Sutomo, Sulistyastuti; Tari, Ezra; Djawa, Maya (Postgraduate School, Universitas Nusa Cendana, 2025)
The Sara Douda dance is a form of oral tradition of cultural arts that combines movement elements from the original dance of the Loli community accompanied by energetic traditional music, namely gongs and drums, as a powerful medium for expressing the experience of faith, namely thanksgiving to the Almighty for giving His grace in the life of Loli society. Sara Douda is full of verbal and non-verbal symbols, rich in meaning, messages and cultural values ​​for the Loli community, used for social interaction and is also an expression of faith to the Highest. To obtain the meaning of symbols in Sara Douda cultural poetry, the author used qualitative methods to search for information related to Sara Douda tradition by conducting interviews in the Tarung-Loli village of West Sumba. The aim of this research is to obtain an overview of the essence, form and meaning of the Sara Douda cultural symbol as a form of expression of art, culture and faith of the Loli people in the study of Contextual Theology with Paul Tillich's perspective which is packaged in the title